Relationship between Helicobacter Pylori Gastritis and Plasma Amino Acids - Derya Altay; Burcu Özşeker Yazman; Merve Başol Göksülük; Mustafa Kendirci; Duran Arslan (Güncel Pediatri)
Introduction: This study investigated the relationship between plasma amino acid levels and the presence of Helicobacter pylori (H. pylori) in children. Materials and Methods: The study included 88 pediatric patients with gastritis (30 H. pylori-positive and 58 H. pylori-negative) and a control group of 32 children. Plasma amino acid levels were assessed using liquid chromatography-tandem mass spectrometry, and dietary amino acid intake for all participants was estimated based on a three-day dietary questionnaire. Results: Plasma glycine, alanine and histidine levels were significantly high in the H. pylori-negative group compared to the other groups (p<0.05). Plasma cysteine, homocysteine and hydroxylysine levels were significantly higher in the control group compared to both gastritis groups (p<0.05). Plasma asparagine, glutamine and histidine levels were found significantly lower in the H. pylori positive group than in the H. pylori negative group (p<0.05). Conclusion: This study identified a moderate correlation between plasma levels of asparagine, glutamine, and histidine and the presence of H. pylori gastritis in children.